Quality evaluation of Kaew Kamin mango with specific gravity at commercial maturity stage - Lueangprasert, Kanyarat; Pattanayaiying, Rinrada; Chuajedton, Angkhana; Choojit, Saovanee; Saelim, Kraiyot (RMUTSB ACADEMIC JOURNAL, 2023)
Kaew Kamin mango is one of the economic important crops of Sa Kaeo province. Generally, Kaew Kamin mango is consumed in the unripe stage with crunchy texture, slightly sour and sweet taste. The best quality of mango depends on suitable harvesting stage (maturity), however most farmers classify the maturity stages by visual assessment which lack of accuracy. Therefore, this research aimed to study in relationship between specific gravity (SG) and physicochemical and physiology properties of the mango quality at commercial maturity stage. Unripe mangoes at commercial maturity stage were cleaned and divided into two groups: floating in water (T1) and sinking in water with floating in 2% sodium chloride (NaCl) solution (T2). The physical, chemical and physiological properties for each mango group were investigated. It was found that fresh weight, total soluble solids content (TSS), titratable acidity content (TA) and moisture content of mangoes varied significantly (p<0.05) with both floating and sinking in water. T2 group was showed the good properties for unripe mangoes, considering as mature. The peel was light green color with L*, a*, b*, C* and H° values of 60.80, -10.06, 36.79, 40.63 and 105.57, respectively. The pulp of mango was orange-yellow color with L*, a*, b*, C* and H° values of 75.30, 3.54, 42.48, 41.97 and 85.94, respectively. Its pulp had high starch concentration and TSS (9.24 °brix). TA and moisture content of T2 group were low values at 3.75% and 85.13%, respectively, which were significantly different compared to T1 group. In conclusion, SG method can be used to separate the Kaew Kamin mangoes quality at commercial maturity stage.